Desempenho de sementes de genótipos de milho infectadas pelo complexo Stenocarpella e potencial de detecção dos patógenos por meio de espectroscopia no infravermelho próximo - Fernandes, Joana Souza (2015)
The tillage technique use, the seed production fields are inclined to fungal attacks more easily. The gender Stenocarpella sp., is composed for two species S. maydis and S. macrospora, causer of white ear rot, stalk rot and leaf spot, they can survive in crop debris causing significant losses in corn. The method used to verify the presence of this fungus in seeds is slow and laborious, so the quality control industry is responsible to provide security in the market of maize seeds. The objective of this research was to verify the performance of maize genotypes seeds infected by the Stenocarpella complex and the potential detection of the pathogens by spectroscopy in the near infrared. The research was carried out at the Seed Analysis Laboratory of the Agriculture Department and at the Seed Pathology Laboratory of the Plant Pathology Department, at the Federal University of Lavras (UFLA). Corn seeds were used of a susceptible genotype, and other tolerant to the studied fungus from the harvest 2013/2014, provided by Dow Agrosciences company. The fungal colony was developed on BDA + manitol media. After growth of the colonies, the seeds were distributed in the medium by different inoculum potential (0, 24, 48, and 72 hours). The determination of physiological quality of seeds was performed by germination test, first germination count, emergency, emergency speed index and cold test. The sanitary quality was determined by "Blotter test" with freezing. The Stenocarpela sp. presence detected by the Polymerase Chain Reaction (PCR), analysis of the isoenzyme esterase (EST), and the sanity test, the results were used as reference for the seed analysis by spectroscopy in the near infrared (NIR). To establish the calibration model was used the regression method by partial least squares with discriminant analysis (PLS DA). It can be concluded that with increasing time of the seed exposure to the inoculum there was a slight reduction in the physiological quality. The PCR is an efficient method for fungus detection to the gender level. The isoenzyme esterase analysis can help in the isolates differentiation of S. maydis and S. macrospora, and the spectroscopy technique in the near infrared (NIR) with the PLS-DA method is promising for the detection and differentiation of the studied fungus.